2021
DOI: 10.1073/pnas.2020705118
|View full text |Cite
|
Sign up to set email alerts
|

Lysergic acid diethylamide (LSD) promotes social behavior through mTORC1 in the excitatory neurotransmission

Abstract: Clinical studies have reported that the psychedelic lysergic acid diethylamide (LSD) enhances empathy and social behavior (SB) in humans, but its mechanism of action remains elusive. Using a multidisciplinary approach including in vivo electrophysiology, optogenetics, behavioral paradigms, and molecular biology, the effects of LSD on SB and glutamatergic neurotransmission in the medial prefrontal cortex (mPFC) were studied in male mice. Acute LSD (30 μg/kg) injection failed to increase SB. However, repeated LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…In line with this, previous studies indicated the effects of tryptamine psychedelics on dimensions related to healthy social functioning such as increased emotional empathy and prosocial behaviour ( Dolder et al, 2016 ; Pokorny et al, 2017 ; Mason et al, 2019 ; Uthaug et al, 2021 ), changes in personality traits agreeableness ( Netzband et al, 2020 ) and compassion ( Apud Peláez, 2020 ), as well as feelings of connection to others ( Watts et al, 2017 ). A recent study in mice reported that repeated administration of low doses of LSD promoted social behaviour by potentiating 5-HT2AR and AMPA receptor neurotransmission in the mPFC via an increasing phosphorylation of the mTORC1 ( de Gregorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, previous studies indicated the effects of tryptamine psychedelics on dimensions related to healthy social functioning such as increased emotional empathy and prosocial behaviour ( Dolder et al, 2016 ; Pokorny et al, 2017 ; Mason et al, 2019 ; Uthaug et al, 2021 ), changes in personality traits agreeableness ( Netzband et al, 2020 ) and compassion ( Apud Peláez, 2020 ), as well as feelings of connection to others ( Watts et al, 2017 ). A recent study in mice reported that repeated administration of low doses of LSD promoted social behaviour by potentiating 5-HT2AR and AMPA receptor neurotransmission in the mPFC via an increasing phosphorylation of the mTORC1 ( de Gregorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychedelic compounds alter social cognitive processes (Table 2) and studies in rodents are beginning to elucidate the underlying mechanistic pathways. A study in male mice showed that repeated doses of LSD (30 µg/kg, daily for 7 days), but not a single dose, resulted in more time interacting with a stranger mouse in the direct social interaction test, associated with potentiation of mPFC excitatory transmission via 5-HT2A and AMPA receptors and via an increasing phosphorylation of the mTORC1 protein (269). Moreover, the inactivation of mPFC glutamate neurotransmission impaired social behavior and negated the prosocial effects of LSD (269).…”
Section: Modulation Of Social Processing Systemsmentioning
confidence: 99%
“…A study in male mice showed that repeated doses of LSD (30 µg/kg, daily for 7 days), but not a single dose, resulted in more time interacting with a stranger mouse in the direct social interaction test, associated with potentiation of mPFC excitatory transmission via 5-HT2A and AMPA receptors and via an increasing phosphorylation of the mTORC1 protein (269). Moreover, the inactivation of mPFC glutamate neurotransmission impaired social behavior and negated the prosocial effects of LSD (269). Another study suggested that psilocybin attenuated some of the sociability deficits in a prenatal valproic acid mouse model of autism (270).…”
Section: Modulation Of Social Processing Systemsmentioning
confidence: 99%
“…Recent work with rodents has unveiled a mechanism of action potentially underlying the prosocial effects of psychedelics. De Gregorio et al (2021b) have demonstrated that repeated administration of low doses of LSD in mice enhances social interaction by potentiating 5-HT 2A and AMPA receptor neurotransmission in the medial prefrontal cortex via an increasing phosphorylation of the mTORC1 (a protein involved in the modulation of social behavior). Moreover, psilocybin has been found to increase striatal dopamine concentrations in humans, a mechanism partly underlying euphoria and depersonalization phenomena ( Vollenweider et al, 1999 ).…”
Section: Psychedelic Instrumentalization In the Human Socio-cognitive Nichementioning
confidence: 99%